Effect of the Combination of Hibiscus sabdariffa in Combination with Other Plant Extracts in the Prevention of Metabolic Syndrome: A Systematic Review and Meta-Analysis - Ana María García-Muñoz; Ana I. García-Guillén; Desirée Victoria-Montesinos; María Salud Abellán-Ruiz; Begoña Alburquerque-González; Fernando Cánovas (Foods, 2023)
Metabolic syndrome is a complex and multifactorial disorder associated with increased risk of cardiovascular disease and type 2 diabetes, exacerbated by a sedentary lifestyle and situations such as the COVID-19 pandemic. Recent studies have shown that consumption of fruits and vegetables high in polyphenols has a protective effect, reducing cardiovascular risk. Hibiscus sabdariffa (HS) in combination with other plant extracts has recently attracted scientists’ attention due to its potential use in the treatment of metabolic syndrome. This systematic review and meta-analysis examines the effects of HS in combination with other plant extracts on the prevention of metabolic syndrome, exploring their synergistic effects and potential as therapeutic agents. For this purpose, a systematic search of randomized clinical trials (RCTs) was conducted in four different databases and the data obtained were then used for a meta-analysis. Initially, the titles and abstracts of 1368 studies were read. From these, 16 studies were examined closely for their eligibility, and finally, seven RCTs with 332 participants were included in both the meta-analysis and the qualitative analysis. Our results show that HS in combination with other plant extracts improved anthropometric parameters, blood pressure, and lipid profile (low density lipoprotein cholesterol and total cholesterol) compared to a placebo control group. It is important to note that although this meta-analysis suggests that HS in combination with other plant extracts may have a beneficial effect on cardiovascular parameters, further research is needed to determine the optimal dose and intake duration.